A Virtual Reality Stroop Art Exergame for Cognitive-Motor Rehabilitation in Chronic Stroke Survivors - Hadjipanayi, Christos; Banakou, Domna; Azhar, Abraiz; Sokratous, Dimitris; Michael-Grigoriou, Despina (My University, 2025)
We are pleased to present these conference proceedings in the VTT Technology series, which contains the papers accepted for the Application Track and Poster & Demo Track of EuroXR 2025, the 22nd annual EuroXR conference, being hosted by ZHAW (School of Management and Law) from September 3rd to September 5th 2025, in Winterthur, Switzerland. This publication is thus a collection of the application papers (talks) and posters and demos papers (posters and demonstrations) presented at the conference. It provides an interesting perspective into current and future applications of VR/AR/MR. In previous years, under the name EuroVR, the conference has been held in Bremen (2014), Lecco (2015), Athens (2016), Laval (2017), London (2018), Tallinn (2019) and Valencia (2020); and as EuroXR in Milan (2021), Stuttgart (2022), Rotterdam (2023) and Athens (2024). The focus of the EuroXR conferences is to present, each year, novel Virtual Reality (VR), Mixed Reality (MR) and Augmented Reality (AR) technologies, including software systems, display technologies, interaction devices, and applications, to foster engagement between industry, academia, and the public sector, and to promote the development and deployment of VR/MR/AR technologies in new, emerging, and existing fields. This annual event of the EuroXR association (https://www.euroxr.org/) provides a unique platform for exchange between researchers, technology providers, and end users around commercial or research applications. We would like to warmly thank the industrial committee chairs for their great support and commitment to the conference, and special thanks go to the local organizing committee for their great effort in making
Keywords: Virtual Reality; XR; virtual worlds; EuroXR association; applications; posters; demos